2003
DOI: 10.1046/j.1537-2995.2003.00494.x
|View full text |Cite
|
Sign up to set email alerts
|

A unique 502C>T mutation in exon 7 of ABO gene associated with the Bel phenotype in Taiwan

Abstract: A novel 502C>T mutation was found in the Bel subgroup in Taiwan and successfully developed a rapid and accurate molecular protocol to detect this mutation. To our knowledge, the new Bel allele that was found is unique in Taiwanese residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 25 publications
1
13
1
Order By: Relevance
“…Using 3D structural analysis, because amino acid substitution at Residue 168 may not alter the active site cleft of the GTB enzyme and the novel R168Q mutant GTB is predicted to form fewer hydrogen bonds than the wildtype GTB, reduced protein stability is a possible explanation of reduced phenotype of the mutant. However, ABO*Bel03 allele (c.502C>T, p.R168W) reported as Bel phenotype 16 is weaker than Bw phenotype of the novel R168Q mutant discovered in this study, although the number of hydrogen bonds found at Residue 168 of the mutants are the same. Since it was insufficient to interpret the weaker expression of B antigen in the R168W mutant compared to the R168Q mutant, we reasoned that steric hindrance plays a role in the decreased protein stability because of the bulkier side chain of W168 residue than that of the Q168 residue.…”
Section: Table 1 the Reported Phenotype Predicted Number Of Hydrogecontrasting
confidence: 65%
See 1 more Smart Citation
“…Using 3D structural analysis, because amino acid substitution at Residue 168 may not alter the active site cleft of the GTB enzyme and the novel R168Q mutant GTB is predicted to form fewer hydrogen bonds than the wildtype GTB, reduced protein stability is a possible explanation of reduced phenotype of the mutant. However, ABO*Bel03 allele (c.502C>T, p.R168W) reported as Bel phenotype 16 is weaker than Bw phenotype of the novel R168Q mutant discovered in this study, although the number of hydrogen bonds found at Residue 168 of the mutants are the same. Since it was insufficient to interpret the weaker expression of B antigen in the R168W mutant compared to the R168Q mutant, we reasoned that steric hindrance plays a role in the decreased protein stability because of the bulkier side chain of W168 residue than that of the Q168 residue.…”
Section: Table 1 the Reported Phenotype Predicted Number Of Hydrogecontrasting
confidence: 65%
“…¶ Previously reported alleles containing the mutation in parenthesis. 16,17 anti-B antisera compared to B3 phenotype of her father. This weaker expression of A and B antigens on the neonate's RBCs is likely due to her young age and is consistent with a previous report of a neonate with the ABO*B305 allele; in that case, despite having a ABO*B305/ABO*O01 genotype, the neonate demonstrated an O phenotype while her adult maternal aunt with a similar genotype, ABO*B305/ABO*O02 allele demonstrated a B3 phenotype.…”
Section: Table 1 the Reported Phenotype Predicted Number Of Hydrogementioning
confidence: 99%
“…The molecular basis underlying many of these B subgroup alleles has been studied and more than 20 B weak (B w ) alleles have been reported so far. [12][13][14][15][16][17][18][19][20][21][22][23] Typically, these phenotypes result from missense mutations at the ABO locus resulting in single amino acid changes in the B-enzyme. Variant glycosyltransferases associated with weak A or B subgroups, however, have not yet undergone structural analysis to resolve the conformational basis for these phenotypes.…”
mentioning
confidence: 99%
“…The O allele causes a frameshift mutation due to a 261 cDNA single nucleotide G deletion, resulting in the formation of a polypeptide chain with sugar-free-transferase activity (Yamamoto et al, 1990). In addition to the three major alleles, more and more alleles related with ABO subtypes are continuously being identified in different races and individuals (Chester and Olsson, 2001;Yip, 2002;Lin et al, 2003;El-Zawahri and Luqmani, 2008;Zhen et al, 2011). Although their frequencies are relatively low, these alternate alleles serologically manifest mainly as differentially expressed ABO blood group antigens and by phenomena such as the weakening of antigen strength, mixed-field-agglutination, and inconsistent positive and negative stereotypes in blood typing (Issitt and Anstee, 1998).…”
Section: Introductionmentioning
confidence: 99%